Handling multiple models of system components in stand-alone photovoltaic system sizing via iterative sizing algorithm. (November 2022) - Othman, Zulkifli; Sulaiman, Shahril Irwan; Musirin, Ismail; Omar, Ahmad Maliki; Shaari, Sulaiman
Abstract: Stand-alone photovoltaic systems have been used widely for rural electrifications. However, the success of the power supply systems is dependent on their technical and economic performance. Also, the system sizing becomes cumbersome when there are many models of systems components that need to be considered during the sizing process. Therefore, this paper presents an iterative-based sizing algorithm for determining the optimal model of each system component, i.e. photovoltaic modules, solar batteries, charge controllers and inverters such that either the performance ratio or the levelized cost of electricity of the system is optimized. The results showed that the iterative-based sizing algorithm required lower computational time than the conventional sizing algorithm using multiple single runs. In addition, the iterative-based sizing algorithm also presented the convenience of sizing based on single run.